Determination of acute lethal doses (LD50 and LC50) of imidacloprid for the native bee Melipona scutellaris Latreille, 1811 (Hymenoptera: Apidae) - Costa, L. M.; Grella, T. C.; Barbosa, R. A. [UNESP]; Malaspina, O. [UNESP]; Nocelli, R. C F (Universidade Estadual de Feira de Santana, 2015)
The bee species Melipona scutellaris Latreille, 1811 (Hymenoptera: Apidae) is native to Brazil and, stingless. In Brazil, stingless bees are responsible for 40% to 90% of tree species pollination, depending on the considered ecosystem. However, their survival has been threatened since the country has been standing out as a big consumer of pesticides. Many of the pesticides used are considered toxic to bees, including imidacloprid. Although the bees are not the target of these substances, they are highly vulnerable to contamination. Thereby, the objective of this study was to establish the mean lethal dose (LD50) and the mean lethal concentration (LC50) of imidacloprid for the M. Scutellaris. In order to carry out this experiment, bees were collected and the test was performed according to OECD's protocol (1998a, 1998b), developed for A. mellifera. For the determination of LD50 and LC50, data was analyzed through the Probit method. The topical LD50 established in this study was 2.41 ng/bee for 24 hours and 1.29 ng/bee for 48 hours. The oral LC50 was 2.01 ng i.a./μL for 24 hours and 0.81 ng i.a./μL for 48 hours. Thus, it is important to establish management methods which take this higher susceptibility into account to protect native species.
Keywords: Neonicotinoid; Stingless bee; Toxicity